Expressivity attributed to music affects the smoothness of bowing movements in violinists - Nicola Di Stefano; Daniela Lo Presti; Luigi Raiano; Carlo Massaroni; Chiara Romano; Emiliano Schena; Marc Leman; Domenico Formica (Scientific Reports)
Abstract Playing music is a complex task that relies on the combination of musicians’ technical and expressive skills. While the literature has investigated the effects of musical expressivity on the listeners, the way how technical difficulty and emotional expressivity affect musicians during playing has surprisingly received no attention. In an attempt to fill this gap in the literature, we collected behavioral and physiological data from twelve violinists playing 29 pieces that included both technical exercises and excerpts from classical repertoire for violin. After playing each stimulus, participants rated it for emotional expressivity and technical difficulty. During the entire session, cardiac parameters and electrodermal activity were collected, together with the kinematic parameters of the bowing gesture. A set of Linear Mixed-Effect (LME) models suggested that emotional expressivity attributed to music affected the fluidity of bowing (i.e., smoothness), with the excerpts rated as more expressive being performed in a less smooth way. In contrast, LME models revealed no effects of expressivity and technical difficulty on any of the physiological parameters of violinists. Our results offer novel insights into the psychophysiological dynamics that link motor parameters with musical expressivity. These findings could influence educational practices in music and deepen our understanding of aesthetic emotions.